OPTIMISING THE ROLE OF THE ISLAMIC SPIRITUAL COMMUNICATION AND CONSULTATION FORUM IN EMBEDDING RELIGIOUS VALUES AMONG CIVIL SERVANTS OF THE NORTH SUMATRA PROVINCIAL GOVERNMENT - Hasibuan, Qori Ananda Azhari; Nasution, Syawaluddin; Ritonga, Hasnun Jauhari (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
This research aims to: (1) To find out the communication synergy carried out by the Communication and Consultation Forum for Islamic Spiritual Guidance (Fokkus Babinrohis) in conveying religious values to the State Civil Apparatus (ASN) within the North Sumatra Provincial Government; (2) To find out the contribution of Fokkus Babinrohis programs and activities in instilling Islamic religious values in ASN behavior; and (3) To find out the challenges faced by Fokkus Babinrohis in building effective communication in religious guidance to ASN. This research used a descriptive method with a qualitative approach. Data collection techniques were conducted through in-depth interviews, observation, and documentation of eleven informants who were directly involved in the forum and policy makers. The results showed that the communication synergy built by Fokkus Babinrohis runs strategically, participatively, and touches the spiritual aspects of ASN through a two-way communication approach and vertical coordination across agencies. Religious programs such as routine recitation, Islamic ethics training, and dakwah safaris make a real contribution to improving ASN morale, discipline, and integrity. However, there are a number of challenges faced, including internal management conflicts, limited facilities and budgets, low ASN participation, and the non-optimal role of rohis units in agencies. For this reason, institutional evaluation, management restructuring, and a more contextual and comprehensive coaching approach are needed to effectively internalize religious values in the bureaucratic environment.